How to draw faces in simple steps in simple steps - Hodge, Susie (Tunbridge Wells (Kent) Search Press, 2013)
The human face is central to art - from childhood it is what we want to draw. Here, Susie Hodge shows how to draw a fantastic selection of faces. Even beginners will be able to create realistic
Drawing
1
Keywords: Drawing -- Technique